SiO2–H3BO3 promoted solvent-free, green and sustainable synthesis of bioactive 1-substituted-1H-tetrazole analogues1. (2nd March 2015) - Parveen, Mehtab; Ahmad, Faheem; Mohammed Malla, Ali; Azaz, Shaista
<x xml:space="preserve">Abstract</x> Eco-friendly and expeditious synthesis of tetrazole derivatives.